Head and neck melanoma: outcome and predictors in a population-based cohort study - Spoerl, Steffen; Spanier, Gerrit; Reiter, Elena; Gerken, Michael; Haferkamp, Sebastian; Grosse, Jirka; Drexler, Konstantin; Ettl, Tobias; Klinkhammer-Schalke, Monika; Fischer, Rene; Spörl, Silvia; Reichert, Torsten E.; et al. (Head & Face Medicine, 2021)
Background To evaluate predictive clinico-pathological characteristics on outcome in head and neck melanoma (HNM) in a population-based study with particular emphasis on the prognostic effect of sentinel lymph node biopsy (SLNB), Charlson comorbidity index (CCI) and distinct tumor localisations. Methods Here we primarily describe a retrospective multicenter population-based cohort study with 402 patients having undergone resection with curative intent of HNM between 2010 and 2017. SLNB was used in the diagnosis of 79 HNM patients. Outcome was analyzed, focusing on SLNB, CCI as well as tumor localisation. Overall survival (OAS) und recurrence free survival (RFS) was examined by uni- and multivariate analysis. Results Histopathologically verified lymph node metastasis according to SLNB was associated with impaired RFS in HNM patients (p = 0.004). Especially in higher tumor stages, the sole implementation of SLNB improved survival significantly in the present cohort (p = 0.042). With most of the HNM being located in the face, melanoma of the scalp and neck could be linked to deteriorated patient's outcome in uni- as well as multivariate analysis (p = 0.021, p = 0.004). Conclusions SLNB is a useful tool in predicting development of distant metastasis after HNM resection with curative intent. Especially in higher tumor stages, performing a SLNB ameliorated survival of HNM patients. Additionally, CCI as well as a distinct tumor localisations in HNM were identified as important risk factors in our population-based cohort study.
CRIS-Team WoS Importer:2021-11-05